Simultaneous assessment of TNF-α, TIM-1, and TLR4 plasma levels for predicting the severity of allergic rhinitis - Zhou, Lijun; Shi, Chenke; Yuan, Feng (Vojnosanitetski pregled, 2026)
Background/Aim. Allergic rhinitis (AR) is a chronic inflammation of the nasal mucosa caused by allergens. To date, some individual biomarkers, such as total immunoglobulin E (IgE), have been shown to be possible factors for the assessment of the severity of AR. The aim of the study was to determine the value of simultaneously measuring the levels of tumor necrosis factor (TNF)-α, T-cell immunoglobulin and mucin domain 1 (TIM-1), and toll-like receptor 4 (TLR4) as predictors of AR severity. Methods. The study included two groups of respondents: the AR group – ARG (n = 96), which consisted of patients with AR treated between March 2021 and May 2023, and the control group – CG (n = 60), which consisted of healthy individuals undergoing physical examinations during the same period. Levels of TNF-α, TIM-1, and TLR4 were compared between the ARG and CG, and their associations with disease severity were analyzed. Results. Logistic regression analysis revealed that elevated eosinophil counts, IgE, TNF-α, TIM-1, and TLR4 levels were independent risk factors for the occurrence of moderate-to-severe AR (odds ratio > 1, p < 0.05). The areas under the receiver operating characteristic curves for plasma TNF-α, TIM-1, and TLR4 levels in predicting disease severity were 0.889, 0.831, and 0.842, respectively, while the combined predictive value reached 0.932, indicating excellent diagnostic performance. Conclusion. The simultaneous measurement of plasma TNF-α, TIM-1, and TLR4 levels provides a novel and reliable approach for predicting the severity of AR. Their combined assessment demonstrates higher predictive accuracy than that of individual markers, offering potential value for disease stratification and clinical decision-making.
Keywords: immunoglobulins; prognosis; rhinitis, allergic; severity of illness index; tumor necrosis factor-alpha.